Clinical Predictors of Symptomatic Versus Asymptomatic Hiatus Hernia in Adults. A Cross-Sectional Analysis - ABADIN, MUHAMMAD ZAIN UL; HUMA FATIMA,; ABDULLAH, HAFIZ MUHAMMAD; RAFAQAT, FARRUKH (Pakistan Journal of Medical & Health Sciences, 2025)
Background: Hiatus hernia is a widely encountered gastrointestinal disorder that could have negative or positive symptomology. The determinants of the occurrence of symptoms amongst the patients are not clear. This research was to find clinical predictors of the difference between symptomatic and asymptomatic hiatus hernia in adults. Methods: A cross-sectional study was done on 100 patients (adults) who had been diagnosed with hiatus hernia on either endoscopy or barium swallow. Clinical evaluation had been used to classify patients as symptomatic (n=62) and asymptomatic (n=38). Demographic data, body mass index correction (BMI), smoking condition, hernia type, and hernia size and existence of esophagitis were taken. Chi-square tests, independent t-tests, and logistic regression were the statistical tests that were used to determine independent predictors of developing the symptoms. Results: BMI (29.6 3.9 vs 26.8 4.2; p=0.002), hernia size (3.4 cm 1.1 vs 2.6 cm 0.8; p=0.001) and esophagitis prevalence (53.2 vs 23.7; p=0.004) were significantly greater in symptomatic patients. Smoking demonstrated a tendency of association, and was not a predictor independently. BMI (OR=1.21, p=0.003), hernia size (OR=1.94, p=0.001) and esophagitis (OR=2.67, p=0.013) were found significant independent predictors of symptomatic presentation using logistic regression. Conclusion: Increased BMI, greater size of hernia and the presence of esophagitis plays significant role in increasing the probability of symptomatic hiatus hernia in the adult population. These predictors can be used to identify a person at high risk at an early stage, personalized lifestyle change, and even better clinical management approaches.